Kompetensi Profesionalisme Guru Dalam Kedisiplinan Mengajar di SMP Negeri 35 Medan - Esra Natasya Sitepu; Ivana Theo Philia; Firdayanti Firdayanti; Jekson Saragih; Laras Sati Sintania; Ture Ayu Situmeang; Jamaludin Jamaludin (Jurnal Yudistira : Publikasi Riset Ilmu Pendidikan dan Bahasa, 2024)
This research discusses teacher professionalism competencies in teaching discipline. Teacher professional competence consists of four aspects: pedagogical, personality, professional and social. Professional teachers have the ability to manage learning, have positive personality strengths, have the ability to master learning material, and have the ability to communicate with students and the community. Teacher discipline includes the level of awareness and willingness of teachers to respect, submit and obey decisions, orders and regulations that apply in the school/madrasah environment. This research was conducted at SMP Negeri 35 Medan. In this research the author used descriptive qualitative methods. The descriptive qualitative research method is a research approach that aims to understand and describe phenomena or events in detail and in depth.